Pemikiran Tasawuf Sosial KH. Bahauddin Nursalim (Gus Baha’) - Miftakhul Munif; Jamal Ma'mur Asmani (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2022)
This study aims to determine the thoughts of KH. Bahaudin Nursalim (Gus Baha') on social Sufism. The object of research is Gus Baha's recitation which is disseminated through Youtube. This study is included in qualitative research with a character study approach. The data collection techniques are through printed and digital documentation, especially Gus Baha's recitation on Youtube as well as books or journals related to the research topic. The results of the study found seven ideas of Gus Baha' social mysticism, namely: all Muslims go to heaven, the recommendation to follow the ulama, surrender is the highest logic, the importance of knowledge, eliminating suspicion in worship, respecting the struggles of others, and not speaking against other religions.